Pengaruh Promosi Dan Electronic Word Of Mouth (E-Wom) Terhadap Keputusan Berkunjung Di Wisata Kampung Lali Gadget Kecamatan Wonoayu Sidoarjo - Putri, Pradina Amanda; Herwati, Andry; Listyawati, Liling (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2024)
This research delves into the impact of Promotion and Electronic Word of Mouth (e-WOM) on Visit Decision at the tourist destination, Kampung Lali Gadget in Wonoayu District, Sidoarjo, both simultaneously and partially, while also identifying the most dominant variable influencing the decision. The study adopts a quantitative approach using multiple linear regression analysis. The target population consists of Kampung Lali Gadget visitors, though the exact number remains undetermined. The primary focus is on visitors who have been to Kampung Lali Gadget within the past three months (July-September 2024), have seen relevant promotions, and engaged in sharing reviews, recommendations, or opinions on social media or other review platforms about this destination. The sampling technique used follows a probability sampling approach, specifically employing cluster random sampling. This choice is due to the undefined quantity of the population, prompting sample size calculation based on Cochran’s formula. The result yielded a sample of 96 respondents. Data analysis was conducted in depth through instrument testing, classical assumption testing, and multiple linear regression. Findings from this study indicate that both promotion and e-WOM exert a positive and statistically significant impact on visit decisions from a simultaneous perspective. However, in a partial perspective, promotion shows a positive and significant effect on visit decisions, while e-WOM, though positively associated, lacks statistical significance in this study. Promotion emerges as the most dominant variable influencing the Visit Decision to Kampung Lali Gadget in Wonoayu District, Sidoarjo. Keywords : Promotion, Electronic Word Of Mouth (e-WOM), Visiting Decision